Cannabinoid Hyperemesis Syndrome: The Missed Diagnosis - João B. Fonseca; Daniela Vilaverde; Rosa Rodrigues; Pedro Morgado (Revista Portuguesa de Psiquiatria e Saúde Mental, 2020)
Cannabis is the most cultivated and abused illicit drug worldwide. Paradoxically to the antiemetic properties attributed to cannabis, a relatively new cannabinoid hyperemesis syndrome (CHS) started to be recognized and is characterized by cyclic vomiting that are interspaced by asymptomatic phases. We present a case of a 36‑year‑old woman who repeatedly presented to the emergency room with cyclic vomiting that alleviated with hot showers. She was a long‑term cannabis user and the diagnosis was only established several years later after the onset of symptoms. The diagnostic work up was unremarkable, and the only effective treatment was cannabis cessation. Hot bathing behavior is a key characteristic of this syndrome. CHS is a new clinical condition that should be considered in a setting of recurrent and intractable vomiting in patients with a history of cannabis use.